To solve the equation \( -2(4x+8)+2x = -5x+10 \), the steps can be arranged in the following order:
- Distribute: \(-8x - 16 + 2x = -5x + 10\)
- Combine Like Terms: \(-6x - 16 = -5x + 10\)
- Get x-terms together on one side: \(-16 = x + 10\)
- Get constants together on one side: \(-26 = x\)
So, the final order of the steps is:
- Distribute: \(-8x - 16 + 2x = -5x + 10\)
- Combine Like Terms: \(-6x - 16 = -5x + 10\)
- Get x-terms together on one side: \(-16 = x + 10\)
- Get constants together on one side: \(-26 = x\)